Initial Pain Management Plans in Response to Severe Pain Indicators on Oncology Clinic Previsit Questionnaires - Michael S Sanatani; Maan Kattan; Dwight E Moulin (Pain Research and Management)
BACKGROUND: The issue of how to address patient pain in the outpatient setting remains challenging. At the London Regional Cancer Program (London, Ontario), patients complete the Edmonton Symptom Assessment System (ESAS) before most visits.